Analisis Semantik Pada Mitos Masyarakat Bugis di Desa Sesulung Kecamatan Pamukan Selatan Kabupaten Kotabaru - Husni Mubarak (STKIP Paris Barantai, 2019)
The formulation of this research problem (1) How is the analysis of denotative meanings in the myths of the Bugis people in the Sesulung Village, South Pamukan Subdistrict, Kotabaru District ?. (2) How is the analysis of the connotative meaning of the myth of the Bugis community in Sesulung Village, South Pamuka Subdistrict, Kotabaru District ?. The purpose of this study is (1) Describe the Denotative Meanings of the Myth of the Bugis Society in Sesulung Village, South Pamukan Subdistrict, Kotabaru Regency. (2) Describe the Conotative Meanings of the Myth of the Bugis Society in Sesulung Village, South Pamukan Subdistrict, Kotabaru District. The method used in this study is a qualitative descriptive method which is a description of the results of the overall analysis of myths in the Bugis community in Sesulung Village, South Pamukan Subdistrict, Kotabaru District. Data collection techniques used are (1) direct observation or observation. (2) interview. (3) documentation. The results of the study show that myths in the Bugis community in Sesulung Village still strongly believe and believe in these myths. This is evidenced by making observations or direct observations and interviews with speakers who really know about myths in Bugis society. The results of the study show that myths in the Bugis community in Sesulung Village, South Pamukan Subdistrict, Kotabaru District, from all the myths that came from myths in Infants, Children, Adolescents, Adults, Pregnant and Elderly Women are only myths in the elderly that contain denotative meaning (true meaning) there is also the myth that you should not wear shorts because it is not worth seeing and may not wear young clothes because it is not clothes that are suitable for him anymore. Whereas the connotative meaning (meaning added value of taste) to myths are all myths that exist in Infants, Children, Adolescents, Adults and Pregnant Women. One of the myths that connotes connotation of the Baby myth, is that it is not permissible to eat sticky babies because babies will get sick at night, in children they should not lie on their stomach because they pray for their mother to die quickly, in adolescents they should not eat small dishes because they will get little money, adults should not lie rolled because their husband will be taken by someone else and the first child will die, and the myth of pregnant women may not sit at the door because it will be difficult to give birth. Keywords: Semantics, Myth, Bugis Society.